Prostate-specific antigen and prostate-specific antigen kinetics in predicting 18F-sodium fluoride positron emission tomography-computed tomography positivity forfirst bone metastases in patients with biochemical recurrence after radical prostatectomy - James Yoon; Leslie Ballas; Bhushan Desai; Hossein Jadvar (World Journal of Nuclear Medicine)
We evaluated the association between serum prostate specific antigen (PSA) level and kinetics to predict 18F-sodium fluoride positron emission tomography-computed tomography (18F-NaF PET-CT) positivity forfirst bone metastases in men with biochemical recurrence after radical prostatectomy. All 18F-NaF PET-CT scans that were performed at our institution during 2010–2014 were queried to find patients who demonstrated biochemical recurrence after radical prostatectomy. Records were reviewed to obtain data on PSA levels and kinetics at the time of 18F-NaF PET-CT and pathologic features of the prostatectomy specimen, which were then used for receiver operating characteristic (ROC) analysis to determine predictability for 18F-NaF PET positivity. Thirty-six patients met our inclusion criteria. Of these, 8 (22.2%) had positive 18F-NaF PET-CT scans. Mean values for PSA, PSA doubling time (PSADT), and PSA velocity (PSAV) were 2.02 ng/ml (range: 0.06–11.7 ng/ml), 13.2 months (range: 1.11–60.84), and 1.28 ng/ml/year (range: 0.1–5.28) for 18F-NaF PET-CT negative scans, and 4.11 ng/ml (range: 0.04–14.38 ng/ml), 8.9 months (range; 0.7–27.8), and 9.06 ng/ml/year (range: 0.04–50.2) for 18F-NaF PET-CT positive scans, respectively (P = 0.07, 0.47, and 0.02, respectively, for PSA, PSADT, and PSAV). ROC analysis for 18F-NaF PET-CT positivity resulted in area under the curve (AUC) values of 0.634 for PSA, 0.598 for PSADT, and 0.688 for PSAV. ROC analysis with combined models gave AUC values of 0.723 for a combination of PSA and PSADT, 0.689 for a combination of PSA and PSAV, and 0.718 for grouping of PSA, PSADT, and PSAV. There was no significant association between 18F-NaF PET-CT positivity and primary tumor Gleason score, TN staging, and status of surgical margins. 18F-NaF PET-CT detectedfirst-time osseous metastases in 22.2% of our patients with biochemical recurrence after prostatectomy with the PSA level range ≤11.7 ng/ml. PSAV was statistically significant in predicting 18F-NaF PET-CT positivity. ROC analysis demonstrated higher AUCs when PSA was combined with PSA kinetics parameters.